Threshold‐based characteristics of apricot frost exposure at young fruit in the warm temperate zone, China. (11th August 2021) - Yang, Jianying; Dong, Hangyu; Huo, Zhiguo; Wang, Peijuan; Yao, Shuran; Wu, Dingrong; Ma, Yuping
Abstract: Late spring frost stress is one of the major environmental limiting factors for apricot in the warm zone in China. Investigation of frost exposure of apricot is of particular interest for estimating the frost risk, thus representing the potential damage for apricot production. In this study, daily minimum temperature ( T min ), disaster and phenological data of apricot from 1981 to 2020 in the warm zone were integrated to explore the temperature threshold on apricot at young fruit, facilitating the assessment of apricot frost exposure ( E ) under the background of climate warming. The daily T min was firstly extracted according to the historical disaster records, to identify the per‐ and ongoing weather conditions of the low‐temperature events. The overall accuracy and Receiver Operating Characteristics curve (ROC) were combined to identify the trigger threshold of apricot frost. 1.9°C was identified as the apricot frost trigger threshold in regional assessment, with relatively higher correct rate for disaster (90.2%) and lower incorrect rate for none‐disaster (23.4%). An area under the ROC curve (AUC) of 0.88 was obtained, demonstrating a good performance of T min as the trigger factor in discriminating between apricot frost and no frost. High frequency of days suffered from apricot and frost exposure at young fruit were mainly found in the northwestern and middle parts of the region, with frequencies of more than 2 days and E more than 3. Regional days suffered from apricot frost and E were found to have a negative trend with slope −0.0317 and −0.789, respectively, whereas the northwest and middle part of the study region were found to have an increasing trend. The results can provide technical and theoretical support for targeted apricot frost detection and risk assessment, and measures for apricot frost prevention and mitigation can be implemented according to the threshold‐based results. Abstract : Daily minimum temperature plays a good performance as the trigger factor in discriminating between apricot frost and no frost. 1.9°C was identified as the apricot frost trigger threshold in regional assessment, with relatively higher correct rate for disaster and lower incorrect rate for none‐disaster. A negative trend was detected for the past four decades, whereas frost exposure for apricot in north part of the warm temperate zone was increased.